A CDH23 missense variant in Beauceron dogs with non-syndromic deafness - Abitbol, Marie; Jagannathan, Vidhya; Lopez, Marie; Courtin, Ambre; Dufaure de Citres, Caroline; Gache, Vincent; Leeb, Tosso (Animal Genetics, 2022)
International audience Congenital coat-colour-related deafness is common among certain canine breeds especially those exhibiting extreme white spotting or merle patterning. We identified a non-syndromic deafness in Beauceron dogs characterised by a bilateral hearing loss in puppies that is not linked to coat colour. Pedigree analysis suggested an autosomal recessive transmission. By combining homozygosity mapping with whole genome sequencing and variant filtering in affected dogs we identified a CDH23:c.700C>T variant. The variant, located in the CHD23 (cadherin related 23) gene, was predicted to induce a CDH23:p.(Pro234Ser) change in the protein. Proline-234 of CDH23 protein is highly conserved across different vertebrate species. In silico tools predicted the CDH23:p.(Pro234Ser) change to be deleterious. CDH23 encodes a calcium-dependent transmembrane glycoprotein localised near the tips of hair-cell stereocilia in the mammalian inner ear. Intact function of these cilia is mandatory for the transformation of the acoustical wave into a neurological signal, leading to sensorineural deafness when impaired. By genotyping a cohort of 90 control Beauceron dogs sampled in France, we found a 3.3% carrier frequency. The CDH23:c.[700C>T] allele is easily detectable with a genetic test to avoid at-risk matings.